La profesión médica en Colombia (1999)
ABSTRACT: This article presents the results of a study carried out with the purpose of knowing the changes that are taking place in the professional paradigm of medicine. It als shows the transformations in the ways in which the service that medicine provides to society is regulated. The articule identifies most important moments in the professionalization of medicine in Colombia and describes the laws that have regulates this practice in the twentieth century. Finally, it describes the situation of medical doctors according to the social security reform, as it is perceived by the interviewed actors.